Housing policies for rental property: growing rentership and initiatives to regulate the real-estate market in Rosario (Argentina), 2003-2023 - Barenboim, Cintia Ariana (2024)
Renting property is a widespread practice in much of Argentina. This paper analyses the mechanisms of renting and initiatives to regulate the rental market in Rosario, the third city with the highest number of tenants in the country (2003-2023). Data from official and unofficial documents and press releases show that national legislation favors the deregulation of the housing market. The scarcity of housing policies for tenants contrasts with the availability of unrented housing due to conflicts and lack of state control over prices, regulation and mediation of contracts. The development of a public policy for this market should include a proposal for taxation of unoccupied housing, social renting and incentives for building new housing to meet rental demand.